2020
DOI: 10.3390/cells9102259
|View full text |Cite
|
Sign up to set email alerts
|

Dynasore Blocks Ferroptosis through Combined Modulation of Iron Uptake and Inhibition of Mitochondrial Respiration

Abstract: Ferroptosis is a form of regulated necrosis characterized by a chain-reaction of detrimental membrane lipid peroxidation following collapse of glutathione peroxidase 4 (Gpx4) activity. This lipid peroxidation is catalyzed by labile ferric iron. Therefore, iron import mediated via transferrin receptors and both, enzymatic and non-enzymatic iron-dependent radical formation are crucial prerequisites for the execution of ferroptosis. Intriguingly, the dynamin inhibitor dynasore, which has been shown to block trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 47 publications
(78 reference statements)
1
22
0
Order By: Relevance
“…As they offer the advantage of a rapid effect, these drugs avoid the manifestation of compensatory trafficking pathways [ 56 ]. However, despite their wide use and their undoubtful inhibitory effect on dynamin, the fact that they are small molecules that could bind to multiple targets raises concerns about possible off-target effects [ 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The most compelling evidence in favor of this concern comes from experiments in dynamin triple knockout cells, where, although lack of all three dynamins did not affect fluid-phase endocytosis and membrane ruffling, dynasore and dyngo robustly inhibited these two processes both in wild-type and in the triple knockout cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As they offer the advantage of a rapid effect, these drugs avoid the manifestation of compensatory trafficking pathways [ 56 ]. However, despite their wide use and their undoubtful inhibitory effect on dynamin, the fact that they are small molecules that could bind to multiple targets raises concerns about possible off-target effects [ 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The most compelling evidence in favor of this concern comes from experiments in dynamin triple knockout cells, where, although lack of all three dynamins did not affect fluid-phase endocytosis and membrane ruffling, dynasore and dyngo robustly inhibited these two processes both in wild-type and in the triple knockout cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dynasore, other dynamin inhibitors, i.e., dyngo 4a and dynole 34-2 [ 19 ], have been widely used to block dynamin-dependent endocytosis, especially when cells are resistant to transfection methods. However, since small molecule inhibitors may bind to multiple targets, it cannot be excluded that these inhibitors exert off-target effects [ 20 , 21 ], similarly to dynasore [ 18 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Here, by comparing the effect of the above drugs in VEGF-induced internalization of VEGFR2 and downstream signaling to ERK1/2 and Akt, we suggest that these inhibitors, besides exerting their specific effect in dynamin-dependent endocytosis, cause inhibitory effects on signaling that are independent of endocytosis; i.e., they are due to off-target effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect interactions through biogenesis or degradation have been shown to require a period of several hours in vitro , and thus, should reflect timescales that differ from direct interactions with mitochondrial energy transduction which are typically much faster [ 93 ]. Supporting evidence for the notion that any of the aforementioned compounds function purely through indirect effects is limited, and follow-up studies have demonstrated some direct effects including inhibitory activity against ETS enzymes and antioxidant activities [ 94 , 95 ]. This highlights that caution should be taken when classifying xenobiotics as indirect effectors of mitochondrial metabolism unless the possibility of direct effects has been ruled out.…”
Section: Xenobiotics As Models For Potential Prescription Drug Effect...mentioning
confidence: 99%
“…Similarly, ferroptosis inhibitors decrease ROS and inflammatory cytokine levels in radiation-induced lung injury (211). Other ferroptosis inhibitors, such as p53, PEBP1, ENPP2, and phospholipase iPLA (2) b, may also serve as radiation protectors (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229). Ferroptosis inducers have the potential to be effective radiosensitizers for radiotherapy (230-248) (Figure 4).…”
Section: C) Ferroptosis In Radiation-induced Digestive Injurymentioning
confidence: 99%